Preliminary evaluation of traffic resilience against potential earthquake in Penang Island - Tey, Li-Sian; Nur Syazwani Roslan,; Shahreena Melati Rhasbudin Shah,; Yee, Hooi Min (Penerbit Universiti Kebangsaan Malaysia, 2024)
When an earthquake occurs in a neighboring country close to Malaysia, such as Indonesia, the tremor can be felt by Malaysians, especially states located along the Straits of Malacca. The epicenter of an active earthquake in the Indian Ocean near northwestern Sumatra, Indonesia triggered a tsunami in December 2004 that hit Penang Island and killed dozens of people and caused minor property damage especially the transportation system. A Quantum Geographic Information System (QGIS), Open Street Maps (OSM), Online Questionnaire Survey, and Literature Review were used to evaluate the preliminary traffic resilience in Penang Island. The presence of fault lines and traffic networks from the secondary data were identified and integrated using GGIS and OSM. The contour results showed that the red zone (most affected) and yellow zone (less affected) were mostly located in the northeast district and the upper half in the southwest district while only a small part was covered with the green zone (not affected) in the southwest district of Penang Island. The factors influencing humans in responding during an earthquake were panic and fear from the point of view of history and general knowledge, as well as announcements and evacuations by the government as the highest votes by online questionnaire survey. Preliminary, the traffic networks with higher probability being affected in the events of earthquake are identified so that further study for the traffic resilience can be carried out.